Mobile Heatlh Berbasis Smartphone untuk Kemampuan Ibu Menyusui secara Eksklusif - Dewi, Mariza Mustika; Ahmaniyah, Ahmaniyah; Rochkmana, Meika Jaya (Wiraraja Medika : Jurnal Kesehatan, 2024)
Educational media in the implementation of exclusive breastfeeding plays a very big role in increasing mothers' knowledge and attitudes in order to give birth to breastfeeding actions and skills. Mobile health or mobile-based health or mhealth is one of WHO's recommendations, namely a form of care in the field of education which is expected to be able to overcome health problems by reducing costs, energy and care time. The aim of this research is to determine the effectiveness of smartphone-based mobile health in improving the ability of breastfeeding mothers. exclusively Method: This research is a literature review. Article searches were carried out using several databases with publications in 2014-2024 with the keywords mobile application for exclusive breastfeeding" or "smartphone to improve knowledge and exclusive breastfeeding" or "telehealth for exclusive breastfeeding". Results: The results of studies that have been carried out show that MHealth can be used as an educational medium to increase coverage of exclusive breastfeeding through increasing knowledge, attitudes and changes in behavior of postpartum mothers. Mhealth can be considered an effective educational medium due to the increasing development of technology and its use, which is cheap, easy and can be taken anywhere. The abstract does not contain citations, formulas, tables and figures. Conclusion: Mhealth can be used as an educational medium to increase coverage of exclusive breastfeeding through increasing knowledge, attitudes and changes in behavior of postpartum mothers